Application of cooperative tax accounting to corporate income tax for fiscal loss compensation - Irina Jacinta Mandaku; Muhammad Ardi Nupi Hasyim (ARKA INSTITUTE, 2022)
Koperasi INTI was a corporate taxpayer who received Tax Compensation for losses in 2016. This research aimed to know the Application of Cooperative Tax Accounting to Corporate Income Tax for Tax Loss Compensation received by Koperasi INTI as a corporate taxpayer. The research method used is descriptive comparative using case study approach. The data used include primary data with interviews and secondary data in the form of commercial and fiscal financial statements from Koperasi INTI. In the results of this research shows that Koperasi INTI in the application of Cooperative Accounting for Tax Loss Compensation (Law No.36 of 2008 Article 6 paragraph (2)) not maximal, because of an recording errors that affect commercial cooperatives for tax costs which should have been zero in 2017 and some SHU (Surplus) allocation costs which are recorded in commercial as operational costs so as to reduce the economic benefits of cooperative members which should be maximized.